(untitled) (Journal of Maternal and Child Health, 2019)
Background: Indonesia is one of the developing countries with complex population problems. According to the Central Bureau of Statistics, the current population in Indonesia in 2016 reached 258,704,986 people. One of the government’s efforts to reduce population growth is Family Planning (KB) program. This study aimed to determine the socioeconomic determinants, social norm, religion on the use of IUD contraceptive among women in Klaten, Central Java, using Theory of Planned Behavior. Subjects and Method: This was a cross-sectional study conducted in 25 community health centers in Klaten, Central Java, from November to December 2018. A sample of 200 women of reproductive age was collected by simple random sampling. The dependent variable was the use of IUD. The independent variables were education, husband support, health personnel support, employment, income, social norm, religion, intention, attitude, perceived behavior control. The data were measured by questionnaire and analyzed by a multilevel logistic regression. Result: The use of IUD was positively influenced by higher education (b= 1.40; 95% CI= 0.12 to 2.78; p= 0.047), strong husband support (b= 1.57; 95% CI= 0.12 to 3.03; p= 0.034), strong health personnel support (b= 1.70; 95% CI= 0.14 to 3.26; p= 0.033), employed (b= 1.50; 95% CI= 0.17 to 2.99; p= 0.047), high income (b= 2.14; 95% CI= 0.36 to 3.92; p= 0.018), supportive social norm (b= 1.50; 95% CI= 0.49 to 2.95; p= 0.043), supportive religion (b= 1.42; 95% CI= 0.12 to 2.84; p= 0.048), intention (b= 1.75; 95% CI= 0.15 to 3.35; p= 0.032), positive attitude (b= 2.16; 95% CI= 0.45 to 3.86; p= 0.013), and perceived behavior control (b= 1.57; 95% CI= 0.29 to 3.11; p= 0.046). Community health center had a contextual effect on the use of IUD contraception with ICC= 10.6%. Conclusion: The use of IUD is positively influenced by higher education, strong husband support, strong health personnel support, employed, high income, supportive social norm, supportive religion, intention, positive attitude, and perceived behavior control. The community health center has a contextual effect on the use of IUD contraception. Keywords: IUD contraceptive, utilization, community health center, multilevel analysis Correspondence: Veronica Fenny Wijaya. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: veronicafenny04@gmail.com.